PEMANFAATAN ASAM SITRAT SEBAGAI ACIDIFIER DALAM PAKAN STEPDOWN PROTEIN TERHADAP PERKEMBANGAN USUS HALUS DAN PERTUMBUHAN BROILER - Imam S; L. D. Mahfudz; N. Suthama (JURNAL LITBANG PROVINSI JAWA TENGAH, 2015)
The study aimed was to evaluate the utilization of citric acid (CA) as an acidifiers in dietary protein stepdown (SDN) on the development of small intestine and growth of broiler. Dietary treatment was initiated when the broiler was 8-day-old with an initial body weight was 186.23±0.68 g. Sources of acidifier were synthetic citric acid (SCA) and lime citric acid (LCA). Protein and metabolizable energy contents of starter period feed was 21.41% and 2856.91 kcal/kg, respectively, for control, and 19.25% and 2884.12 kcal/kg, for SDN, while those of finisher period was similar to those of SDN feed of starter period, for control, and 17.37% and 2882.13 kcal/kg, respectively, for SDN. The treatment consisted of T0 (control without SDN and CA), T1 (SDN without CA), T2 (SDN+0.8% LCA), T3 (SDN+ 0.4% SCA), T4 (SDN+0.8% SCA), T5 (SDN+1.2% SCA) and T6 (SDN+1.6% SCA). Parameters observed were development of of the small intestine (weight and length) and final body weights. The study was assigned in a completely randomized design (CRD) with 7 treatments and 4 replicates (6 birds each). The results showed that inclusion of citric acid as an acidifiers in dietary protein stepdown of starter and finisher periods significantly (p<0.05) increased the weight and length of the small intestine (duodenum, jejunum and ileum) with the highest value were T4 (16,72; 32,52; and 26,98 g and 36,22; 83,62; and 78,95 cm) and T5 (15,28; 29,70; and 22,95 g and 35,38; 79,88; and 77,10 cm), while the lowest was T1 (11,00; 22,85; and 16,60 g and 31,50; 70,95; and 65,05 cm) and the highest final body weights were T5 (1048,97 g) and T6 (1074,36 g), while the lowest was T1 (938,43 g). Conclusion of the study is that dietary inclusion of citric acid as an acidifiers in protein stepdown for starter and finisher periods at the level of 0.8 to 1.2% effectively increase weight and length of small intestine, especially duodenum and final body weight of broilers.